“Eine Kneipe ist wie ein Film” - Aproximações entre o cinema de Fatih Akin e o Neuer Deutscher Film de três décadas atrás - Linck, Gabriela Wondracek (Contingentia, 2010)
Fatih Akin has been the subject of much research in the academic world, especially regarding his portrayal of young Turkish Germans, Turkey and the borders between Europe and the Middle East. This article presents a critical evaluation of these approaches and then looks into Akin’s relation with music, literature and the New German Cinema from the 1970’s and 80’s.